(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
: research into and informed discussion of teaching young learners is on the increase, perhaps mirroring the increasing numbers of children learning English globally in primary schools. This introductory article reviews key themes and issues in the teaching of English to young learners, and explains how the articles in this Special Issue connect to and develop them. It also points forward to some of the areas we expect to be of interest to researchers and practitioners in the years to come.